Pelaksanaan Terapi Pijat Bayi pada Nenonatus dengan Hiperbilirubin - Riska Fauziah Nurmala; Siti Yuyun Rahayu; Chatarina Surya; Henny Suzana Mediani; Murtiningsih Murtiningsih (Jurnal Keperawatan Silampari, 2022)
This study aims to identify the implementation of various infant massage therapies in neonates to reduce bilirubin levels using the scoping review method. The research method used in this research is a scoping review that follows the JBI methodology guidelines with searches conducted in several databases, namely PubMed, Web of Science, EMBASE, and Google Scholar. The results showed 12 articles involving 665 neonates in five countries, nine with a randomized control trial (RCT) design, and three quasi-experimental studies. In conclusion, the mechanism of infant massage therapy that most underlies the reduction of neonatal jaundice in the group receiving massage therapy is the stimulation of bowel movements. Keywords: Hyperbilirubin, Neonate, Infant Massage Therapy